Preparation and application of Nb2O5-doped nano disc-shaped MOF derivative composite material
Preparation by the high-energy ball milling method of Nb2O5-doped nanodisc MOF-derived composite material and MgH2, the problem of poor stability and slow hydrogen release rate during the circulation process was solved, and its hydrogen storage performance was significantly improved.
Patent Information
- Application Number
- CN202411616935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The existing MgH2 hydrogen storage materials have poor stability during the cycle process, slow hydrogen release rate and poor kinetic performance, resulting in insufficient hydrogen storage performance in practical applications.
Nb2O5 doped nanodisc MOF-derived composite material was prepared by hydrothermal and calcining technology, and mixed with MgH2 by high-energy ball milling method to prepare MgH2-Nb2O5/MIL-125 composite material, to prepare MgH2-Nb2O5/MIL-125 composite material to Improve its hydrogen absorption and discharge performance.
The initial hydrogen release temperature of MgH2 is significantly reduced, the hydrogen release rate and kinetic performance are improved, the cyclic stability of the hydrogen storage material is enhanced, and the performance is best when the doping amount is 6 wt%.
Smart Images

Figure CN119456045A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen storage materials for designing new energy materials, and specifically to a preparation method and application of a Nb2O5-doped nano-disc-shaped MOF-derived composite material. Background Art
[0002] With the progress and development of society, energy consumption continues to increase, bringing a series of serious environmental pollution problems and energy crises. Therefore, it is urgent to develop new energy sources that are abundant in reserves, clean, efficient, safe and economical. Hydrogen energy has the advantages of abundant reserves, high calorific value and good environmental protection, and is considered to be one of the most promising clean energy sources.
[0003] Solid-state hydrogen storage is the storage of hydrogen in solid materials through physical adsorption or chemical reaction. It has the advantages of safety and high hydrogen storage density. It is the most promising type of hydrogen storage method. Among the many solid-state hydrogen storage materials, magnesium-based hydrogen storage material MgH2 has a high hydrogen storage capacity (theoretical mass hydrogen storage density is 7.6wt%, theoretical volume hydrogen storage density is 110kg / m 3 ), excellent cycle performance, abundant resources, and low price are considered to be one of the most promising hydrogen storage materials, but the good thermodynamic stability and poor kinetic performance limit its wide application.
[0004] In order to improve the hydrogen storage performance of MgH2, researchers from various countries have focused on alloying, nano-sizing and catalyst doping, and have made significant progress. Catalyst doping has been proven to be the most effective way to improve the dehydrogenation / hydrogenation kinetics of MgH2. Currently, researchers have studied various catalysts, including transition metals, transition metal oxides and transition metal carbides. Transition metal oxides play an effective catalytic role in accelerating the hydrogen desorption of MgH2. They can be reduced to low-valent metal oxides or zero-valent metals in the dehydrogenation / hydrogenation cycle. Multivalent metal ions as Mg 2+ and H - The oxygen vacancies on the metal oxide surface are also considered to be efficient sites for promoting MgH2 dehydrogenation, because surface oxygen vacancies can participate in many chemical reactions catalyzed by metal oxides. Therefore, the oxygen vacancy concentration of transition metal oxide catalysts is crucial for the improvement of hydrogen storage kinetics.
[0005] Metal-organic frameworks (MOFs) are a type of crystalline porous material with a periodic network structure formed by self-assembly of metal ions and organic ligands. They can adsorb and desorb hydrogen. The presence of the MOF structure can further enhance the catalytic activity of transition metal compounds by improving the hydrogen diffusion within the bulk MgH2 through increased transfer channels. At the same time, TiO2 in MIL-125 mainly provides more oxygen vacancies for the system.
[0006] MOF derivatives doped with transition metal oxide Nb2O5 as a catalyst composite material showed good hydrogen storage performance. The oxygen vacancies therein provided active sites for hydrogen adsorption and also provided a transfer path for hydrogen migration, thus improving the hydrogen storage performance of the composite material.
[0007] Prior art Zhang et al. (Green Energy & Environment, 2023, DOI: (10.1016 / j.gee.2021.09.004) used a one-pot hydrothermal method to synthesize Nb2O5 nanoparticles with an average particle size of 10 nm and loaded them on a rhombic dodecahedral metal-organic framework (MOF). The hydrogen storage performance of MgH2 was significantly improved. 7wt% Nb2O5@MOF-doped MgH2 began to desorb hydrogen at 181.9°C.
[0008] According to the above research, transition metal oxides can effectively improve the hydrogen storage performance of MgH2.
[0009] On this basis, Lan et al. (Chemical Engineering Journal, 2023, DOI: 10.1016 / j.cej.2023.143692) used metal organic framework (MOF) as a precursor to prepare carbon nitride nanosheets co-doped with disc-shaped nickel and nano-titanium dioxide (Ni, TiO2CN) to improve its hydrogen storage performance. The starting temperature of MgH2 was reduced to 204°C, which was about 104°C lower than that of ball-milled MgH2, but there was still a certain gap with its ideal performance.
[0010] Therefore, through a reasonable preparation method, the structure of the catalyst was successfully controlled, making it appear to be a disc with a thickness of 100-200nm. This structure can act as a grinding aid during the ball milling process, further reducing the initial hydrogen desorption temperature of MgH2, thereby improving the performance of the material.
[0011] The above work reports respectively use Nb2O5 to load on rhombic dodecahedral metal organic frameworks and nickel-based, nano-titanium dioxide (Ni, TiO2CN) doped into disc-shaped metal organic frameworks, and then doped with MgH2 for modification or synergistic catalysis to improve the comprehensive performance of MgH2. However, the hydrogen storage performance of MgH2 is still insufficient in practical applications and needs to be further improved. Therefore, the following problems need to be solved:
[0012] 1. Hydrogen storage materials have poor stability during the cycle;
[0013] 2. The hydrogen storage material has a slow hydrogen release rate during the hydrogen release process;
[0014] 3. The problem of poor kinetic performance of hydrogen storage materials during hydrogen release. Summary of the invention
[0015] The purpose of the present invention is to provide a preparation method and application of a Nb2O5-doped nano-disc-shaped MOF-derived composite material.
[0016] Based on the applicant's work and the research and analysis of the above technical solutions, the following conclusion can be drawn: the current research on the preparation method of transition metal oxides is still unable to achieve a significant improvement in the performance of MgH2.
[0017] Therefore, the present invention aims at the existing technical problems in the field of hydrogen storage and adopts a method with other preparation conditions to achieve the following invention objectives:
[0018] Nb2O5 / MIL-125 was obtained by doping Nb2O5 with nanodisc-shaped MOF-derived composite materials, and then 6wt% of the catalyst was mixed with MgH2 under Ar atmosphere, and the MgH2 composite material was prepared by grinding it with a planetary ball mill. Nb2O5 / MIL-125 can effectively improve the hydrogen absorption and desorption properties of MgH2.
[0019] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:
[0020] Nb2O5 was doped into disc-shaped MIL-125 as a catalyst. The preparation process was simple, with Nb, Ti and O as the main components of the catalyst. Nb2O5 / MIL-125 was obtained through a one-step hydrothermal and calcination technique.
[0021] Wherein, the Nb2O5 / MIL-125 is synthesized by hydrothermal and tubular furnace calcination, and the microscopic morphology is disc-shaped nanosheets with an average diameter of 200nm and an average thickness of 60nm, which makes the ball milling effect more ideal and helps to evenly distribute Nb2O5 / MIL-125 on the MgH2 matrix;
[0022] The base materials of the composite material are niobium pentoxide, terephthalic acid, methanol, N,N-dimethylformamide and tetrabutyl titanate.
[0023] A method for preparing Nb2O5 / MIL-125 doped with MgH2 comprises the following steps:
[0024] Step 1: Obtain Nb2O by hydrothermal method and tubular furnace calcination 5 / MIL-125 composite material.
[0025] Step 2: Prepare MgH2-Nb2O5 / MIL-125 composite material by high energy ball milling.
[0026] Further, the specific process of step 1 is to measure a fixed amount of N, N-dimethylformamide and methanol, stir for 30 minutes, add a fixed amount of terephthalic acid, ultrasonicate for 30 minutes, stir for 1 hour to obtain a clear solution, then add a fixed amount of tetrabutyl titanate, continue to stir for 1 hour to obtain a mixed solution, add a fixed amount of niobium pentoxide, stir for 30 minutes, transfer the solution into a high-pressure reactor for hydrothermal treatment for a period of time, filter, wash and dry the precipitate obtained by hydrothermal treatment, and finally calcine in a tubular furnace to obtain Nb2O 5 / MIL-125 composite material.
[0027] Furthermore, N,N-dimethylformamide is 45 mL, methanol is 5 mL, terephthalic acid is 12 mmol, tetrabutyl titanate is 3 mmol, and niobium pentoxide is 1 mmol.
[0028] Furthermore, the autoclave treatment condition is to keep the temperature at 150°C for 20 hours. The filtration and washing conditions are to use N,N-dimethylformamide for filtration and washing for 3 times and anhydrous ethanol for filtration and washing for 1 time. The drying condition is to dry at 80°C for 12 hours. The tubular furnace calcination condition is in a hydrogen-argon mixed gas atmosphere, the treatment temperature is 550°C, and the reaction time is 2 hours.
[0029] Furthermore, the specific process of step 2 is to mix the Nb2O5 / MIL-125 and MgH2 obtained in step 1 in a certain mass ratio, and then perform ball milling under certain conditions to obtain the Nb2O5 / MIL-125 doped with MgH2 hydrogen storage material.
[0030] Furthermore, the mass fractions of Nb2O5 / MIL-125 are 2wt%, 4wt%, 6wt% and 8wt% respectively, and the ball milling conditions are as follows: argon is used as the protective atmosphere, the ball-to-material ratio is 40:1, the ball milling speed is 400-450r / min, and the ball milling time is 10h.
[0031] The composite material obtained by the present invention is a Nb2O5 doped nano-disc-shaped MOF-derived composite material Nb2O5 / MIL-125. The beneficial technical effects are as follows:
[0032] The Nb2O5-doped nanodisc-shaped MOF-derived composite material was tested by electron microscopy, and it can be seen that the composite material is a disc-shaped nanosheet with an average diameter of 200nm and an average thickness of 60nm.
[0033] TPD detection of MgH2-xNb2O5 / MIL-125 shows that when the doping amount of the composite material is 6wt%, the initial dehydrogenation temperature of the system drops to 165.5℃ and the dehydrogenation amount reaches 6.9wt%.
[0034] The pressure-composition-temperature (PCT) test of MgH2-6 Nb2O5 / MIL-125 hydrogen storage material shows that during isothermal dehydrogenation, the system can completely dehydrogenate at 325°C, and the amount of hydrogen released within 6 minutes reaches 6.6wt%; during isothermal hydrogen absorption, 5.2wt% of hydrogen can be absorbed within 10 minutes at 150°C.
[0035] Therefore, the Nb2O5-doped nano-disc-shaped MOF-derived composite material of the present invention has the following advantages over the prior art:
[0036] 1) The oxygen vacancies in transition metal oxides and the special structure of metal-organic frameworks enhance the adsorption performance of MgH2.
[0037] 2) The initial dehydrogenation temperature of the MgH2-Nb2O5 / MIL-125 composite material synthesized by the present invention after ball milling with MgH2 is 165.5°C, which is lower than the value reported in the above literature.
[0038] Therefore, compared with the prior art, the present invention has a better effect on improving the hydrogen storage performance of MgH2 and has a broader application prospect in the field of hydrogen storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 XRD pattern of the Nb2O5 / MIL-125 composite material prepared in Example 1;
[0040] Figure 2 This is a scanning electron microscope image of the Nb2O5 / MIL-125 composite material prepared in Example 1;
[0041] Figure 3 , 4 TPD curves of ball-milled MgH2, MgH2-6Nb2O5 and MgH2-xNb2O5 / MIL-125 composites with different doping amounts prepared in Example 1.
[0042] Figure 5This is a test diagram of isothermal hydrogen desorption performance at different temperatures of the MgH2-6Nb2O5 / MIL-125 composite material prepared in Example 1;
[0043] Figure 6 This is a test diagram of the isothermal hydrogen absorption performance of the MgH2-6Nb2O5 / MIL-125 composite material prepared in Example 1 at different temperatures;
[0044] Figure 7 This is a test diagram of isothermal hydrogen release performance at different temperatures of ball-milled MgH2 prepared in Example 1;
[0045] Figure 8 This is a test diagram of isothermal hydrogen absorption performance of ball-milled MgH2 prepared in Example 1 at different temperatures;
[0046] Fig. 9 The JMAK model and Arrhenius plot of the MgH2-6Nb2O5 / MIL-125 composite material prepared in Example 1 at different temperatures;
[0047] Fig.10 The JMAK model and Arrhenius plot of ball-milled MgH2 prepared in Example 1 at different temperatures;
[0048] Fig.11 This is a bar chart of the hydrogen desorption cycle life of the MgH2-6Nb2O5 / MIL-125 composite material prepared in Example 1. DETAILED DESCRIPTION
[0049] The present invention is further described in detail through embodiments and in conjunction with the accompanying drawings, but the present invention is not limited thereto.
[0050] Example 1
[0051] This embodiment provides a method for preparing a Nb2O5-doped nanodisc-shaped MOF-derived composite material, and the preparation method includes the following steps.
[0052] Step 1) Preparation of Nb2O5 precursor: First, 9.6 g of hydrated niobium oxalate and 0.355 g of ammonium oxalate were dissolved in 50 mL of deionized water, ultrasonically dispersed, and magnetically stirred until completely dissolved. Then, the solution was transferred into a 100 mL high-pressure reactor, kept at 180° C. for 24 h, cooled naturally to room temperature, and the hydrothermal sample precipitate was collected;
[0053] Step 2) Preparation of Nb2O5: Cross-wash with deionized water and anhydrous ethanol several times, collect the centrifuged sample, and then dry it in a vacuum drying oven at 60°C for 24 hours to obtain a Nb2O5 precursor. Subsequently, the sample is transferred into a muffle furnace, calcined for 2 hours in an air atmosphere, and collected after naturally cooling to room temperature to obtain Nb2O5.
[0054] Step 3) Preparation of Nb2O5 / MIL-125: First, 45 mL of N,N-dimethylformamide and 5 mL of methanol were stirred for 30 min, then 1.9936 g of terephthalic acid was added, ultrasonicated for 30 min, stirred for 1 h, and after complete dissolution, 1 mL of tetrabutyl titanate was measured and ultrasonicated for 1 h, and then 0.2658 g of Nb2O5 obtained in step 1 was added to the mixed solution, stirred for another 30 min, and finally the mixed solution was transferred to a high-pressure reactor and kept at 150 ° C for 20 h. After naturally cooling to room temperature, the hydrothermal sample precipitate was collected. The sample was washed with N, N-dimethylformamide three times by suction filtration, and then washed with anhydrous ethanol once by suction filtration. The washed sample was collected and then dried in a vacuum drying oven at 80°C for 12 h. After drying, the sample was ground into powder and then moved into a tube furnace and calcined at 550°C for 2 h in an atmosphere of hydrogen and argon mixed gas. After naturally cooling to room temperature, the sample was collected and transferred to a glove box filled with Ar for further use.
[0055] In order to prove that the Nb2O5 / MIL-125 composite material was successfully prepared in step 3, XRD test was performed. The test results are shown in Figure 1 As shown, the PDF cards of Nb2O5 and TiO2 (the main component of MIL-125 is TiO2) are in good agreement (PDF#27-1003 and PDF#71-1166). The test results show that Nb2O5 / MIL-125 has been successfully synthesized with high purity and high crystallinity.
[0056] In order to verify the microstructure of Nb2O5 / MIL-125 obtained in step 4, SEM test was carried out. The test results are shown in Figure 2 As shown, SEM testing showed that the microstructure of Nb2O5 / MIL-125 was disc-shaped nanosheets with an average diameter of 200 nm and an average thickness of 60 nm.
[0057] A preparation method of a MgH2-based hydrogen storage material based on Nb2O5 / MIL-125, namely, application of a disc-shaped Nb2O5 / MIL-125 composite material as a catalyst for a MgH2 hydrogen storage material. The specific preparation method comprises the following steps: the Nb2O5 / MIL-125 addition amount is 6wt% under an argon atmosphere throughout the process; after mixing the Nb2O5 / MIL-125 with MgH2, high-energy ball milling is performed under the conditions of a ball-to-material ratio of 40:1, a ball milling speed of 450r / min, and a total ball milling time of 10h; wherein the high-energy ball milling method is a forward and reverse ball milling method, a single ball milling time is 12min, and a ball milling intermittent stop time is 6min, so as to obtain a MgH2-based hydrogen storage material with a Nb2O5 / MIL-125 addition amount of 6wt%, which is named as MgH2-6Nb2O5 / MIL-125.
[0058] In order to prove the hydrogen storage performance of MgH2-6Nb2O5 / MIL-125 composites, TPD test and PCT test were carried out.
[0059] In order to prove the starting dehydrogenation temperature and dehydrogenation amount of MgH2-6Nb2O5 / MIL-125 composite material, TPD test was carried out on the hydrogen storage material. The test results are shown in Figure 3-4 As shown, the initial hydrogen desorption temperature of the hydrogen storage material with a catalyst doping amount of 6wt% is as low as 165.5°C, and the maximum hydrogen desorption amount can reach 6.9wt%.
[0060] In order to prove the hydrogen absorption and desorption ability of MgH2-6Nb2O5 / MIL-125 composite materials at different temperatures, isothermal hydrogen absorption / desorption tests were carried out on the hydrogen storage materials, such as Figure 5-6 As shown in the figure, it can be seen that in the isothermal hydrogen absorption test, MgH2-6Nb2O5 / MIL-125 can absorb 4.7wt% of hydrogen within 30 minutes at 100°C; in the isothermal hydrogen desorption test, it can also release 4.8wt% of hydrogen within 30 minutes at a lower dehydrogenation temperature of 250°C, and when it reaches 325°C, it can basically achieve complete hydrogen desorption within 10 minutes.
[0061] In order to prove the stability of the catalytic active material of the MgH2-6Nb2O5 / MIL-125 composite material, the cycle performance of the hydrogen storage material was tested. The specific test method is: PCT is used to test the cycle performance at 325°C, and the hydrogen pressure of hydrogenation is 3Mpa. The test analysis results are as follows: Fig.11 As shown, after 10 cycles, the actual hydrogen capacity of MgH2-6Nb2O5 / MIL-125 remained at 6.539wt%, which was equivalent to a capacity retention rate of 96.3% compared with the first cycle capacity, indicating that MgH2-6Nb2O5 / MIL-125 exhibited a stable dehydrogenation phenomenon and had good cycle stability.
[0062] In order to demonstrate the influence of Nb2O5 / MIL-125 and Nb2O5 on the hydrogen storage performance of MgH2, comparative examples 1 and 2 are provided, wherein comparative example 1 compares the initial dehydrogenation temperature, hydrogen absorption and dehydrogenation performance and activation energy at different temperatures of MgH2-6Nb2O5 / MIL-125 and ball-milled MgH2 as hydrogen storage materials, and comparative example 2 compares the initial dehydrogenation temperature of MgH2-6Nb2O5 / MIL-125 and MgH2-6Nb2O5 as hydrogen storage materials.
[0063] Comparative Example 1
[0064] A method for preparing a MgH2 hydrogen storage material, wherein the steps not specifically described are the same as those in Example 2, except that: during the ball milling process, no Nb2O5 / MIL-125 is added as a catalyst, that is, only 0.5 g of MgH2 is weighed for ball milling, and the obtained MgH2 hydrogen storage material is referred to as ball milled MgH2. The composite material MgH2-6Nb2O5 / MIL-125 and ball milled MgH2 are subjected to TPD, PCT and activation energy tests.
[0065] The TPD test results of MgH2-6Nb2O5 / MIL-125 and ball-milled MgH2 are shown in Figure 3 As shown in Figure 2, the initial dehydrogenation temperature of ball-milled MgH2 is 274.7°C, and the initial dehydrogenation temperature of the composite material is further reduced to 165.5°C after adding Nb2O5 / MIL-125. Figure 5-6 As shown in the figure, the MgH2-6Nb2O5 / MIL-125 composite material releases 6.2wt% of hydrogen in 20 minutes at 275℃; at 100℃, it can absorb 4.7wt% of hydrogen within 30 minutes. Compared with ball-milled MgH2, which releases 1.9wt% of hydrogen within 20 minutes at 300℃ and absorbs 0.27wt% of hydrogen within 30 minutes at 150℃, the activation energy test results are shown in the figure. Figure 9-10 As shown, the activation energy of ball-milled MgH2 is 128.11 kJ / mol, while the activation energy of MgH2-6Nb2O5 / MIL-125 is 78.06 kJ / mol, which is 50.05 kJ / mol lower than that of ball-milled MgH2.
[0066] Comparative Example 2
[0067] A method for preparing a MgH2-6Nb2O5 composite material, wherein the steps not specifically described are the same as those of Example 2, except that Nb2O5 synthesized in step 2 of Example 1 is added to obtain MgH2-6Nb2O5. The composite materials MgH2-6Nb2O5 / MIL-125 and MgH2-6Nb2O5 are subjected to TPD tests.
[0068] The TPD test results of MgH2-6Nb2O5 / MIL-125 and MgH2-6Nb2O5 are as follows Figure 3 As shown in the figure, it can be seen that the initial dehydrogenation temperature of MgH2-6Nb2O5 is 66.1℃ higher than that of MgH2-6Nb2O5 / MIL-125.
[0069] Combining the results of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, it can be seen that the initial dehydrogenation temperature of MgH2-6Nb2O5 / MIL-125 is reduced by 66.1°C and 109.2°C respectively compared with MgH2-6Nb2O5 and ball-milled MgH2. At 275°C, the MgH2-6Nb2O5 / MIL-125 composite material releases 6.2wt% of hydrogen in 20 minutes; at 100°C, the amount of hydrogen absorbed can reach 4.7wt% within 30 minutes. At 300°C, the ball-milled MgH2 releases 1.9wt% of hydrogen within 20 minutes, and absorbs 0.27wt% of hydrogen within 30 minutes at 150°C. The activation energy of MgH2-6Nb2O5 / MIL-125 is 78.06kJ / mol, which is 50.05kJ / mol lower than that of ball-milled MgH2.
[0070] In summary, the addition of Nb2O5 / MIL-125 significantly improves the hydrogen storage performance of MgH2. When the doping amount is 6wt%, the initial hydrogen desorption temperature is the lowest and the performance is the best.
Claims
1. A method for preparing a Nb2O5-doped nanodisc-shaped MOF-derived composite material, characterized in that: The specific steps include: Step 1): prepare a mixture of N, N-dimethylformamide and methanol, and stir for 15-30 minutes; Step 2): add terephthalic acid to the mixed solution, ultrasonicate for 15-30 min, and stir for 1-3 h; Step 3): adding tetrabutyl titanate to the mixed solution and ultrasonicating for 1-3 hours; Step 4): adding niobium pentoxide to the mixed solution, wherein the amount of niobium pentoxide is 1 mmol, and stirring for 15-30 minutes; Step 5): the mixed solution obtained in step 4) is transferred into a stainless steel reactor, and heated in a constant temperature drying oven at a predetermined heating temperature to react to obtain a precipitate; Step 6): The precipitate obtained in step 5) is filtered and washed with N, N-dimethylformamide and anhydrous ethanol, respectively, and then placed in a vacuum oven for vacuum drying at a predetermined drying temperature to obtain a powdery precursor; Step 7): Place the powdered precursor obtained in step 6) in a tube furnace and calcine at a predetermined calcination temperature for 2-4 hours to obtain a Nb2O5-doped nano-disc-shaped MOF-derived composite material.
2. The method for preparing the Nb2O5-doped nanodisc-shaped MOF-derived composite material according to claim 1, characterized in that: In the step 1), the ratio of N,N-dimethylformamide to methanol is 9:
1.
3. The method for preparing the Nb2O5-doped nanodisc-shaped MOF-derived composite material according to claim 1, characterized in that: The ratio of terephthalic acid to tetrabutyl titanate in step 2) and step 3) is 4:
1.
4. The method for preparing the Nb2O5-doped nanodisc-shaped MOF-derived composite material according to claim 1, characterized in that: The predetermined heating temperature in step 5) is 150° C., and the insulation time is 20 h.
5. The method for preparing the Nb2O5-doped nanodisc-shaped MOF-derived composite material according to claim 1, characterized in that: The predetermined drying temperature in step 6) is 60-100° C., and the drying time is 12 hours.
6. The method for preparing the Nb2O5-doped nanodisc-shaped MOF-derived composite material according to claim 1, characterized in that: The calcination temperature in step 7) is 550° C. and the calcination time is 1-3 hours, so as to obtain a Nb2O5-doped nano-disc-shaped MOF-derived composite material.
7. An application of a Nb2O5-doped nanodisc-shaped MOF-derived composite material obtained by the preparation method according to any one of claims 1 to 6, characterized in that: Used to improve the hydrogen storage performance of MgH2.
8. The use of a Nb2O5 doped nanodisc-shaped MOF-derived composite material according to claim 7, characterized in that: When the catalyst doping amount is 6wt%, the initial dehydrogenation temperature drops to 165.5℃, and the dehydrogenation amount reaches 6.6wt% at 300℃. During isothermal dehydrogenation, the system can completely dehydrogenate at 325℃, and the maximum dehydrogenation amount can reach 6.6wt% within 6min. During isothermal hydrogen absorption, the system can absorb 5.1wt% hydrogen within 40min at 100℃. The activation energy of hydrogen release is 50.05 kJ·mol -1 , after 10 cycles, it is 96% of the initial use.
Citation Information
Cited By
Preparation method of iodine element and carbon nanotube co-doped n-type PbTe thermoelectric material
CN120817805A